Encyclopaedia of women health and empowerment - 6 Childbirth and postnatal care Management of critical care, miscarriages and diseases - Ganguly, N. K.; Kumar, Meenal; Kumar, R. (New Delhi Deep & Deep Publications, 2009)
Normal childbirth and caesarean delivery